Effect of Vacuum-Packed Refrigeration Storage on Low-FatAntioxidant-Rich Kadaknath Chicken Sausages - Patel, Divyanee; Nayak, Narendra Kumar; Chauhan, Pranav; Vipin Kumar Gupta,, (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This study aimed to investigate the impact of vacuum-packed refrigeration storage on quality of low-fat-antioxidant rich Kadaknath chicken sausages. The study examined the changes in physico-chemical, microbiological properties and sensory attributes. The pH, TBA and FFA values were lower as compared to control throughout the storage. A progressive and significant (P
Keywords: Antioxidant; Kadaknath; Low fat; Sausage; Vacuum packaging